Identification, Characterization and Rescue of a Novel Vasopressin-2 Receptor Mutation Causing Nephrogenic Diabetes Insipidus - Ranadive, Sayali A. (Clin Endocrinol (Oxf), 2008)
OBJECTIVE: X-linked nephrogenic diabetes insipidus (XNDI), caused by mutations in the V2 vasopressin receptor (V2R), is clinically distinguished from central diabetes insipidus (CDI) by elevated serum vasopressin (AVP) levels and unresponsiveness to 1-desamino-8-D-arginine vasopressin (DDAVP). We report two infants with XNDI, and present the characterization and functional rescue of a novel V2R mutation. PATIENTS: Two male infants presented with poor growth and hypernatremia. Both patients had measurable pre-treatment serum AVP and polyuria that did not respond to DDAVP, suggesting NDI. However, both also had absent posterior pituitary bright spot on MRI, which is a finding more typical of CDI. METHODS: The AVPR2 gene encoding V2R was sequenced. The identified novel missense mutation was re-created by site-directed mutagenesis and expressed in HEK293 cells. V2R activity was assessed by the ability of transfected cells to produce cAMP in response to stimulation with DDAVP. Membrane localization of V2R was assessed by fluorescence microscopy. RESULTS: Patient 1 had a deletion of AVPR2; patient 2 had the novel mutation L57R. In transiently transfected HEK293 cells, DDAVP induced detectable but severely impaired L57R V2R activity compared to cells expressing wild-type V2R. Fluorescence microscopy showed that myc-tagged wild-type V2R localized to the cell membrane while L57R V2R remained intracellular. A non-peptide V2R chaperone, SR121463, partially rescued L57R V2R function by allowing it to reach the cell membrane. CONCLUSIONS: L57R V2R has impaired in vitro activity that can be partially improved by treatment with a V2R chaperone. The posterior pituitary hyperintensity may be absent in infants with XNDI.